Fuzzy regions in an intrinsically disordered protein impair protein–protein interactions. (12th January 2016) - Gruet, Antoine; Dosnon, Marion; Blocquel, David; Brunel, Joanna; Gerlier, Denis; Das, Rahul K.; Bonetti, Daniela; Gianni, Stefano; Fuxreiter, Monika; Longhi, Sonia; Bignon, Christophe
Abstract : Despite the partial disorder‐to‐order transition that intrinsically disordered proteins often undergo upon binding to their partners, a considerable amount of residual disorder may be retained in the bound form, resulting in a fuzzy complex. Fuzzy regions flanking molecular recognition elements may enable partner fishing through non‐specific, transient contacts, thereby facilitating binding, but may also disfavor binding through various mechanisms. So far, few computational or experimental studies have addressed the effect of fuzzy appendages on partner recognition by intrinsically disordered proteins. In order to shed light onto this issue, we used the interaction between the intrinsically disordered C‐terminal domain of the measles virus (MeV) nucleoprotein (NTAIL ) and the X domain (XD) of the viral phosphoprotein as model system. After binding to XD, the N‐terminal region of NTAIL remains conspicuously disordered, with α‐helical folding taking place only within a short molecular recognition element. To study the effect of the N‐terminal fuzzy region on NTAIL /XD binding, we generated N‐terminal truncation variants of NTAIL, and assessed their binding abilities towards XD. The results revealed that binding increases with shortening of the N‐terminal fuzzy region, with this also being observed with hsp70 (another MeV NTAIL binding partner), and for the homologous NTAIL /XD pairs from the Nipah and Hendra viruses. Finally, similar results were obtained when the MeV NTAIL fuzzy region was replaced with a highly dissimilar artificial disordered sequence, supporting a sequence‐independent inhibitory effect of the fuzzy region. Abstract : Intrinsically disordered proteins (IDPs) play a crucial role in protein–protein and protein–DNA recognition. Many IDPs undergo a disorder‐to‐order transition on binding their biological targets, but others remain considerably disordered, resulting in a "fuzzy" complex. Here, the authors investigated the effect of fuzzy regions flanking molecular recognition elements on the binding of IDPs to partners. They show that interaction between the intrinsically disordered C‐terminal domain of the measles virus nucleoprotein (NTAIL ) and the X domain of the viral phosphoprotein, its structured binding partner, increased with progressive shortening of the NTAIL fuzzy region. This suggests that fuzzy regions in IDPs negatively regulate protein–protein interactions.